2008
DOI: 10.1093/chemse/bjn040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Identified Mitral and Tufted Cells in Freely Breathing Rats: II. Odor-Evoked Responses

Abstract: Mitral and tufted cells are the 2 types of output neurons of the main olfactory bulb. They are located in distinct layers, have distinct projection patterns of their dendrites and axons, and likely have distinct relationships with the intrabulbar inhibitory circuits. They could thus be functionally distinct and process different aspects of olfactory information. To examine this possibility, we compared the odor-evoked responses of identified single units recorded in the mitral cell layer (MCL units), in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…The linkages appear to be somewhat tighter in tufted-tufted pairs, which had smaller mean width and lag of narrow peaks in cross-correlograms, significantly correlated firing or bursting patterns, and perhaps stronger mean electrical coupling. In contrast to previous studies of evoked responses of mitral and tufted cells in vivo (Nagayama et al, 2004; Griff et al, 2008), we did not detect significant differences between basal spontaneous firing rates of mitral and tufted cells in slices. Thus, the two cell types may express divergent spike activity only when relaying signals that encode odorant stimuli.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The linkages appear to be somewhat tighter in tufted-tufted pairs, which had smaller mean width and lag of narrow peaks in cross-correlograms, significantly correlated firing or bursting patterns, and perhaps stronger mean electrical coupling. In contrast to previous studies of evoked responses of mitral and tufted cells in vivo (Nagayama et al, 2004; Griff et al, 2008), we did not detect significant differences between basal spontaneous firing rates of mitral and tufted cells in slices. Thus, the two cell types may express divergent spike activity only when relaying signals that encode odorant stimuli.…”
Section: Discussioncontrasting
confidence: 99%
“…3 and Table I. Previous studies showed that tufted cells responded more robustly to odorant stimuli in vivo, and they may be under weaker inhibitory control (Griff et al, 2008; Nagayama et al, 2004). We expected to see this reflected in the spike activity in slices.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Tufted cells, a cell type that we did not target in the current study, are more abundant than MCs (Shepherd et al, 2004), and could carry information on odor identity. Middle tufted cells respond to odors and local processing of the odorant signal in the middle tufted cells differs from that in MCs (Griff et al, 2008; Nagayama et al, 2004). In addition, external tufted cells whose cell bodies lie adjacent to glomeruli could transmit information on odor identity (Wachowiak and Shipley, 2006), although whether these cells can carry information to higher order centers has not been fully explored (Schoenfeld and Macrides, 1984; Schoenfeld et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…One explanation for this result may be that the AON receives input preferentially from OB tufted (as opposed to mitral) cells (Haberly and Price, 1977; Scott et al, 1980; Scott, 1981; Macrides and Schneider, 1982; Nagayama et al, 2010; Sosulski et al, 2011). Functionally, tufted cells are more excitable, have higher firing frequencies and display stronger respiratory locking compared to mitral cells (Schneider and Scott, 1983; Ezeh et al, 1993; Nagayama et al, 2004; Griff et al, 2008; Burton and Urban, 2014) and so may preserve the timing of odor sampling more faithfully across their population. Inhalation-coupled feedback from AON may play several roles in shaping how the OB processes incoming olfactory information.…”
Section: Discussionmentioning
confidence: 99%